Profile of Neuromuscular Disorders: Neurology Clinic, Tripoli Children Hospital - Eshrif, Seham; Alghareeri, Suhaylah; BenAmer, Fatma; Elsheikh, Sondos (Ibnosina Journal of Medicine and Biomedical Sciences, 2023)
Objective Neuromuscular disorders (NMDs) are any diseases affecting the lower motor neuron (anterior horn cell, peripheral nerve, and neuromuscular junction) or muscle, all of which are components of motor unit. The aim of this study was to describe the clinical, demographic, and genetic profile of children diagnosed with different NMDs.Materials and Methods Descriptive case series study where clinical records for children with neuromuscular disorders (NMDs) how presented to the outpatient Neurology Clinic at Tripoli Children Hospital in the period from January 2015 to the date of data collection May 2023 have been reviewed to obtain the relevant information which include demographic data, parental consanguinity, family history of affected other members, diagnostic groups within NMDs used were spinal muscular atrophy (SMA) and its subtypes, Duchenne muscular dystrophy (DMD), limb girdle muscular dystrophy (LGMD) and any other NMDs, genetic testing results, ambulatory state at the time of data collection, age at death if occurred, mode of treatment (steroid for patients with diagnosis of DMD, oral Risdiplam/IV Zolgensma/intrathecal Spinraza for patients with SMA) and Genetic testing results and the eligibility to spesfic exon skipping therapy for DMD patients.Results The study revealed 53 patients with NMDs, which represent 3.8% of all neurological disorders. Of these, 32 (60.4%) were males and 21 (39.6%) were females. Patient ages ranged between 2 months and 20 years (mean = 10 years). SMA and DMD are more common than the other disorders. 77.4% of patients were have positive consanguinity and 66% are have family history. 54.7% of patients still have ability to walk independently. Four (7.5%) patients were died three of them were have diagnosis of SMA type 1 and they died before age of 18 months and the fourth who has diagnosis of SMA type 3 was die at age of 12 years.Conclusion Although neuromuscular disorders are rare as individual disease entities, as a group they are not. The retrospective study presented here could form the backbone of a future Libyan neuromuscular registry, which is necessary with many novel NMD therapies in pipeline.
Keywords: neuromuscular disorders; spinal muscular atrophy; Duchenne muscular dystrophy; limb girdle muscular dystrophy; novel NMD therapies